Modelling the characteristics of flour from wheat and orange fleshed sweet potato using simplex lattice design for chin-chin production - Oladeji, Funmilola Grace; Oyedokun, James; Akinwande, Bolanle Aishat; Ade-Omowaye, Beatrice Iyabo Olayemi (Bangladesh Journal of Scientific and Industrial Research, 2024)
Optimized composite flour from wheat flour (WF) and orange fleshed sweet potato (OFSP) meal was used for the production of chin-chin. The roots of OFSP were washed, air-dried, peeled, sliced to 1 cm thick, dried at 50 oC for 18 h and then milled to pass 200 µm sieve aperture to obtain OFSP flour. Composite flours (CF) were formulated from OFSP and WF using Simplex Lattice Design (SLD) and its characteristics were analyzed and modelled. The indices for validating the models showed adequacy of the models. The CF had improved water absorption capacity, oil absorption capacity and beta-carotene. Meanwhile, optimization of relevant properties resulted in an optimized CF which comprised 12.5% OFSP flour and 87.5% WF. The sensorial scores of chin-chin from the optimized CF indicated acceptability by the taste panelists. Chin-chin from the optimized CF would contribute to beta-carotene intake of consumers while reducing wheat importation. Bangladesh J. Sci. Ind. Res. 59(3), 159-168, 2024